ANALISIS PENGARUH KOMPENSASI KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - JUMAGI; Siregar, Edi (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
This research is motivated decline in employee performance PT.Detede. This study aimed to examine the effect of labor compensation, motivation and work discipline, to employee performance in PT. Detede. Research data retrieval is done through questionnaires to 65 respondents employees PT. Manunggal Metalindo Karsa obtained by using the technique jenuh sampling. Then analysis of quantitative and qualitative data. Qualitative analysis is the interpretation of the data obtained from the respondents and the data obtained from the field. Data - data that has met the validity, reliability, and classical assumption, processed with SPSS (Statistical Package for Social Science) for Windows 15. Where hypothesis testing using t test showed that the three independent variables are labor compensation (X1), work discipline (X2), and the work discipline (X3) significant positive effect on employee performance dependent variable (Y).